2021
DOI: 10.21273/horttech04682-20
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Management Practices for Commercial Tigernut Production in Southern Ontario, Canada

Abstract: To foster development of Ontario commercial tigernut (Cyperus esculentus var. sativus) production, this study was conducted to identify cultural management practices that increase tuber yields. The agronomic practices of field preparation (hilled vs. not hilled), regular irrigation vs. natural rainfall, varying rates of nitrogen (N) fertility, and early season weed management were evaluated. Irrigation had no significant impact on total fresh weight, dry weight, and marketable yield over 2 growing seasons. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…It is also worth mentioning that no emergence of volunteer tigernut was noted during the season after the production year at any of the locations where the study was conducted. This is in agreement with a similar observation by Elford et al (2020) in Ontario, and it suggests that development of tigernut production in New Jersey would not lead to the establishment of volunteer weedy tigernut in subsequent crops. However, the most challenging weeds to control with plasticulture-grown tigernut would remain yellow nutsedge and purple nutsedge because the pointed shoot tip of both species allow them to penetrate the polyethylene barrier and directly compete with the crop.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It is also worth mentioning that no emergence of volunteer tigernut was noted during the season after the production year at any of the locations where the study was conducted. This is in agreement with a similar observation by Elford et al (2020) in Ontario, and it suggests that development of tigernut production in New Jersey would not lead to the establishment of volunteer weedy tigernut in subsequent crops. However, the most challenging weeds to control with plasticulture-grown tigernut would remain yellow nutsedge and purple nutsedge because the pointed shoot tip of both species allow them to penetrate the polyethylene barrier and directly compete with the crop.…”
Section: Resultssupporting
confidence: 92%
“…Based on the results of these studies, oxyfluorfen alone or mixed with pendimethalin applied at transplanting shows promise as an effective residual herbicide treatment for weed control and good quality tuber yield comparable to the yield in weed free plots. Elford et al (2020) reported a 2-to 3week weed-free period for preventing tigernut yield loss. Results of this study show that oxyfluorfen applied PRE would provide effective weed control up to 8 weeks after treatment in fields where hairy galinsoga is not a weed of concern and fulfills the requirement of a weed-free period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirmed that tigernut cultivation for the tuber is feasible in NJ and growers may take full advantage of this crop as an addition to the agricultural economy of the state. In Canada, Elford et al [ 35 ] reported successful production of tigernuts under Ontario conditions. Added to the increasing popularity of tigernut production in Mexico [ 22 , 36 ], it seems north America (Canada, Mexico, and USA) now has the potential to contribute significantly to the global tigernut production in the future.…”
Section: Discussionmentioning
confidence: 99%